CLINICAL RECOMMENDATIONS FOR AUTOLOGOUS PLATELET DERIVATIVES USED IN PERIODONTAL REGENERATION - Sofia Iozon; Alexandra Roman; Andrada Şoancă (Amaltea Medical Publishing House, 2018)
The main goal of periodontal regenerative techiques is to recreate the soft and hard lost tissues for functional and aesthetic reasons. Because of the complexity of this proccess (multiple celular types that need to be stimultated in a particular time sequence for recreation of all four periodontal tissues), periodontal regenerative techniques are still inconsistant and unpredictable. In the last decades, the tendency in surgical periodontal approaches is to use autologous products like platelet concentrates, because of their high content in growth factors that improve the healing proccess and promote tissue regeneration. The existing scientific proofs on this matter are yet insufficient for reliable clinical conclusions upon the use of platelet concentrates in periodontal surgical therapy.